High-light-intensity photoassociation in a Bose-Einstein condensate - Gasenzer, Thomas (Physical review. A, Atomic, molecular, and optical physics, 2004)
We investigate theoretically the molecular yield in photoassociation of Bose-Einstein condensed sodium atoms for light intensities of the order of and above those applied in a recent experiment. Our results show that the rate at which ground-state molecules may be formed saturates at high light intensities whereas the loss rate of condensate atoms does not. This is caused by the opposing roles of the short- and long-range pair correlations present near resonance under the influence of the laser and is crucial for the development of efficient photoassociation procedures in a condensate.
Gesehen am 16.08.2019